Actual problems of realizing the social rights of people with epilepsy: legal aspect - A. P. Gertsen; V. V. Rumyantsev (Русский журнал детской неврологии)
Epilepsy is a disease creating multiple obstacles for patients in terms of their social rights as well as for their associates. The level of physician’s legal literacy can both improve the life of a patient with epilepsy and significantly complicate it for many years. Despite the existing normative legal acts regulating the admission of patients with epilepsy and epileptic syndrome to various types of work, military service, weapon possession, and driving, there are still many questions, which is a significant defect in medical service. First of all, we should take into account that people with long-term remission (with or without pharmacotherapy) have the same legal restrictions as patients with incurable epilepsy. Therefore, accurate initial diagnostics in patients with symptoms similar to epilepsy is very important.This article describes the main legislative rules regulating social rights of people with epilepsy and draws attention of the medical community to the problems of these patients.